Numerical Simulation of Conjugate Forced Turbulent Heat Convection with Induced Natural Laminar Convection in a 2d Inner Cavity - Vasco-Calle, D (Elsevier Masson SAS, 2015)
Unsteady natural convection process of a fluid inside an inner walled vessel caused by an external forced turbulent convective flow of air in a rectangular duct has been analyzed numerically for Re Combining double low line 5000; Re Combining double low line 22,000. Fluid mechanics and conjugate convective heat transfer, for both inner fluid (water) and outer fluid (air), described in terms of continuity, linear momentum, k-σ turbulence model and energy equations were predicted by using the finite-volume method (FVM). Results for the streamlines, isotherms, local Nusselt numbers along the cavity walls and the average friction factor are presented. A comparison between obtained results for both Reynolds number is made. In general, it was found that the cooling process is improved up to 79% when Re number is increased from 5000 to 22,000; and the fluid mechanics characteristics inside the vessel is not considerable affected by the velocity inlet of the cooling air. © 2014 Elsevier Masson SAS.